Clinical and economic profile of entecavir in the treatment of chronic hepatitis b virus infection - Eandi, Mario (Farmeconomia. Health economics and therapeutic pathways, 2011)
HBV infection in Italy is frequently underestimated, raising the risk of important complications, such as cirrhosis and hepatocellular carcinoma, and thus increasing mortality. In infections phases requiring treatment, it’s possible to choose among the currently available drugs: interferons, nucleoside and nucleotide analogues. Entecavir is a nucleoside analogue able to maintain a high genetic barrier, and to reduce the viral load < 300 copies/ml in 67% of HBeAg-positive patients and in 90% of HBeAg-negative patients after 48-weeks treatment, improving also necroinflammatory grade and fibrosis degree. In spite of the high cost of the confection, entecavir induces a saving in health costs because of the decrease in the disease progression. If compared, through pharmacoeconomic models and analysis, to tenofovir, a nucleotide acid considered equivalent in the first-line monotherapy of HBeAg-positive patients and in the long-term treatment of HBeAg-negative patients by the current international and Italian guidelines, it seems favourable in terms of safety and consequently in terms of costs of adverse events spared. However further studies are required: in particular direct comparative studies are still lacking.